The effects of diamond mining on the people of Bocha: a case study of Chiadzwa from 2009-2016 - Mutahwa, Rumbidzai (Midlands State University, 2017)
This research seeks to explore the effects of formal diamond mining on the community of Chiadzwa. The research seeks to assess the challenges and problems that the community of Chiadzwa faced from 2009-2015 which emanated from the formalized diamond mining in Chiadzwa.2009 marked a turnaround in the diamond mining spectrum ,diamond mining in Chiadzwa shifted from illegal to legal or formalized diamond were companies such as Mbada, Anjin acquired mining claims from the Ministry of Mines .Mining in many countries such as Botswana served as one of the major contributing economic activity to the country’s Gross Domestic Project (GDP).Minerals such as diamonds if managed properly can positively change the lives of the community and their environments . However, one cannot underestimate its impacts particularly negative impacts (harm) on the community’s social .economic, cultural, environmental and political life although mining sector contributes to the country’s economy .These impacts can change the way of life of individuals, thus calls for attention. Due to the formalized mining high rates of unemployment, poverty, land degradation, cultural erosion, social disintegration and outbreak of diseases have put the Chiadzwa community in danger and have called for stakeholder participation and mechanisms that mitigate these impacts. Effects of formal diamond mining outweighs the potential socio-economic and environmental benefits of diamond mining on the community hence the role of the government and other relevant stakeholders as enforcers of laws, regulations and policies need to be clearly defined for the benefit and the protection of the community. In an effort to divulge the effects of diamond mining on the community the researcher used a qualitative research design. Interviews and focus groups were of great importance to the researcher. The researcher employed simple random sampling.